Monitoring Ecological Condition in the Western United States 2000
DOI: 10.1007/978-94-011-4343-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Physical, Chemical, and Biological Indicators of Water Quality to a Gradient of Agricultural Land Use in the Yakima River Basin, Washington

Abstract: Abstract. The condition of25 stream sites in the Yakima River Basin, Washington, were assessed by the V.S. Geological Survey's National Water-Quality Assessment Program. Multimetric condition indices were developed and used to rank sites on the basis of physical, chemical, and biological characteristics. These indices showed that sites in the Cascades and Eastern Cascades ecoregions were largely unimpaired. In contrast, all but two sites in the Columbia Basin ecoregion were impaired, some severely. Agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 16 publications
1
56
0
1
Order By: Relevance
“…Inorganic nitrogen in freshwaters occurs in three different forms, Over all classification accuracy = 91.45% namely ammonia, nitrates and nitrites. Agricultural as well as horticultural land practices in the immediate catchment has a direct effect on the nitrogen and phosphorus content in the water body whose loading may lead to nutrient enrichment and the deterioration of the water quality (Harding et al 1999;Cuffney et al 2000). Higher concentration of these nitrogenous forms is attributed to the use of fertilizers in and around the lakes and the addition of Parameters: 1 = water temperature; 2 = pH; 3 = dissolved oxygen; 4 = chloride; 5 = free carbon dioxide; 6 = total alkalinity; 7 = ammoniacal nitrogen; 8 = nitrate nitrogen; 9 = orthophosphate; 10 = total phosphate; 11 = agricultural land; 12 = alpine grassland; 13 = built up; 14 = dense forest; 15 = forest plantation; 16 = horticultural land; 17 = snow-covered/glacial area; 18 = sparse forest; 19 = wasteland; 20 = water bodies and 21 = wetland.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic nitrogen in freshwaters occurs in three different forms, Over all classification accuracy = 91.45% namely ammonia, nitrates and nitrites. Agricultural as well as horticultural land practices in the immediate catchment has a direct effect on the nitrogen and phosphorus content in the water body whose loading may lead to nutrient enrichment and the deterioration of the water quality (Harding et al 1999;Cuffney et al 2000). Higher concentration of these nitrogenous forms is attributed to the use of fertilizers in and around the lakes and the addition of Parameters: 1 = water temperature; 2 = pH; 3 = dissolved oxygen; 4 = chloride; 5 = free carbon dioxide; 6 = total alkalinity; 7 = ammoniacal nitrogen; 8 = nitrate nitrogen; 9 = orthophosphate; 10 = total phosphate; 11 = agricultural land; 12 = alpine grassland; 13 = built up; 14 = dense forest; 15 = forest plantation; 16 = horticultural land; 17 = snow-covered/glacial area; 18 = sparse forest; 19 = wasteland; 20 = water bodies and 21 = wetland.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of annual mean levels of ammoniacal nitrogen, site VI ranked the highest, followed by sites III, I, V, IV and II in decreasing order. Site VI lying on the Wular periphery catchment has the maximum agricultural (r = 0.580) as well as horticultural land (r = 0.919), depicting collinear relationship of ammoniacal nitrogen with the aforesaid parameters (Harding et al 1999;Cuffney et al 2000). The concentration and rate of supply of nitrate nitrogen are intimately connected with the land use practices of the surrounding watershed (Horne and Goldman 1994).…”
Section: Resultsmentioning
confidence: 99%
“…C2 and C3 are considered as the two categories causing the main alteration of stream ecological status according to large scale statistical analyses (Allan, 2004). Agricultural practices on land adjacent to streams can lead to soil erosion and subsequent runoff of fine sediments, nutrients, and pesticides (e.g., Cuffney et al, 2000;Schulz and Liess, 1999). Urbanization leads to enhanced runoff, channel erosion, and reduced water quality due to inputs of metals, oils, and road salts (e.g., Booth and Jackson, 1997;Hammer, 1972;Paul and Meyer, 2001).…”
Section: Land Cover Pressure Typologymentioning
confidence: 99%
“…Various studies have demonstrated negative relationships between biological indices and the percentage of agricultural land in the catchment or gradients of agricultural intensity (Roth, Allan & Erickson, 1996;Walser & Bart, 1999;Cuffney et al, 2000). These impacts are dependent on the different categories of production: many authors designate intensive agriculture as a cause of degradation in stream habitats (Allan & Johnson, 1997;Allan, 2004).…”
Section: Hierarchy Of Impacts: Urbanization Vs Agriculturementioning
confidence: 99%